2007
DOI: 10.1111/j.1574-695x.2007.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined serum IgG response toHelicobacter pyloriVacA and CagA predicts gastric cancer

Abstract: Helicobacter pylori is a major factor for the development of gastric cancer. The aim of this study was to define serum antibody patterns associated with H. pylori infection in patients with gastric cancer using a Western blot technique. Serum samples collected from 115 patients with gastric cancer and 110 age- and gender-matched patients without gastrointestinal diseases were tested for IgG antibodies to H. pylori antigens (outer membrane proteins and whole cell preparations). No significant differences were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Some studies have even found stronger associations for gastrointestinal disease among individuals with VacA antibodies than among those with CagA antibodies (32, 33, 34). However, overall, the findings for the association of VacA antibodies and gastrointestinal pathology are inconsistent, with studies that find positive associations with disease (32, 34, 35) and those that find null associations (31, 36). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have even found stronger associations for gastrointestinal disease among individuals with VacA antibodies than among those with CagA antibodies (32, 33, 34). However, overall, the findings for the association of VacA antibodies and gastrointestinal pathology are inconsistent, with studies that find positive associations with disease (32, 34, 35) and those that find null associations (31, 36). …”
Section: Discussionmentioning
confidence: 99%
“…In regards to gastric cancer, serum antibodies to both CagA and VacA have been found to be associated with increased risk of disease as well as a stronger inflammatory response (31). Some studies have even found stronger associations for gastrointestinal disease among individuals with VacA antibodies than among those with CagA antibodies (32, 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Concordance between histology and serology varied between 95% and 100%. A Scandinavian study [61] with an in‐house Western blot assay compared the banding pattern of 115 gastric cancer patients and 110 without cancer and found that cancer patients had significantly more often antibodies to the 94 kDa protein and to the 30 kDa (UreA) as well as a combination of antibodies to the 85 kDa (VacA) and the 120 kDa (CagA).…”
Section: Noninvasive Methodsmentioning
confidence: 99%
“…The 1DE western blotting technique is a very useful tool for seroepidemiological survey, since it detects both former and current H. pylori infection. Exhaustive studies were performed to explore the seroprevalence of the two main H. pylori antigens, CagA and VacA, and their role as risk factors for H. pylori-related gastric diseases [15][16][17]. However, the association between the seroreactivity to these two antigens and the clinical outcomes of the infection is still controversial [18], and varies among geographical regions and ethnic groups [19].…”
Section: Protein Virulence Factors and Diagnosis Of Infectionmentioning
confidence: 99%